2019
DOI: 10.1111/vec.12815
|View full text |Cite
|
Sign up to set email alerts
|

Detection of endotoxin in plasma of hospitalized diarrheic calves

Abstract: Objectives: To investigate whether lipopolysaccharide (LPS) is present in plasma of calves with naturally occurring diarrhea. The second objective was to determine whether plasma [LPS] correlates with clinical, hematological, biochemical, and acid-base variables, and whether [LPS] differs between surviving and nonsurviving diarrheic calves. Setting: Veterinary teaching hospital. Animals: Thirty-four calves <28 days old admitted for diagnosis and treatment of diarrhea and 30 healthy control calves. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…This finding is in line with experimental studies in pigs and rats, where a hypoglycemic response was observed after induction of peritonitis and sepsis by means of cecal puncture and ligation or intraperitoneal administration of an Escherichia coli culture (Kazarian et al, 1994;Liao et al, 2013;Maitra et al, 2000). Previous studies further reported an association between hypoglycemia and endotoxemia, sepsis, and systemic inflammatory response syndrome in critically ill calves (Lofstedt et al, 1999;Trefz et al, 2016;Gomez et al, 2019). Generalized peritonitis was also found in 37% of severely hypoglycemic hos-pitalized neonatal calves (Trefz et al, 2016), and investigations in adult cattle have shown that septic peritonitis is associated with decreased glucose concentrations in peritoneal fluid and an increased blood-to-peritoneal fluid glucose difference (Wittek et al, 2010).…”
Section: Jdssupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is in line with experimental studies in pigs and rats, where a hypoglycemic response was observed after induction of peritonitis and sepsis by means of cecal puncture and ligation or intraperitoneal administration of an Escherichia coli culture (Kazarian et al, 1994;Liao et al, 2013;Maitra et al, 2000). Previous studies further reported an association between hypoglycemia and endotoxemia, sepsis, and systemic inflammatory response syndrome in critically ill calves (Lofstedt et al, 1999;Trefz et al, 2016;Gomez et al, 2019). Generalized peritonitis was also found in 37% of severely hypoglycemic hos-pitalized neonatal calves (Trefz et al, 2016), and investigations in adult cattle have shown that septic peritonitis is associated with decreased glucose concentrations in peritoneal fluid and an increased blood-to-peritoneal fluid glucose difference (Wittek et al, 2010).…”
Section: Jdssupporting
confidence: 88%
“…Aside from l-LAC, determination of plasma glucose concentrations (GLUC) might have utility in predicting the outcome of affected calves because hypoglycemia was found to be associated with low survival rates and serious conditions such as peritonitis or clinical evidence of sepsis in critically ill neonatal calves (Trefz et al, 2016(Trefz et al, , 2017. Hypoglycemia was also observed during experimentally induced sepsis or endotoxemia in calves (Constable et al, 1991a;Kinsbergen et al, 1994a;Ballou et al, 2011), and a recent study reported a negative correlation between plasma endotoxin and GLUC in neonatal diarrheic calves (Gomez et al, 2019). Similar to l-LAC, the availability and validation of glucometers such as the Freestyle Optium Neo H (Abbott) device allow for calf-side measurement of blood glucose concentrations (Karapinar et al, 2020) and could therefore assist in the clinical decision-making process.…”
Section: Jdsmentioning
confidence: 99%
“…A possible explanation for postoperative hyper-llactatemia in calves with a NO was likely endotoxemia and sepsis due to gastrointestinal organ damage and a concomitant dysfunction of the blood-gut barrier as indicated by the results of necropsy examinations or intraoperative findings of calves that underwent relaparotomy. Endotoxemia and sepsis are well-known contributors to hyperlactatemia (Tennant et al, 1973;Corley et al, 2005;Gomez et al, 2019) as they can lead to microcirculatory dysfunction (Ince, 2005), sequestration of leukocytes with increased glucose turnover during oxidative burst (Haji-Michael et al, 1999), and altered cellular respiration. The latter has been related to a phenomenon called cytopathic hypoxia and was also observed during in vitro studies of cells that were exposed to pro-inflammatory cytokines (Fink, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…31,33 Similarly, the USI variability between analyzers can also have prognostic implications. In human and bovine medicine, there is data suggesting that the high USI values are associated with the presence of endotoxin in diarrheic calves 34 and that USI concentrations can predict the outcome (hospital survival) in critically ill children 35 and calves with diarrhea. 30 In horses, the concentration of USI (measured as strong ion gap, SIG) was greater in nonsurviving than surviving hospitalized foals.…”
Section: Discussionmentioning
confidence: 99%